2017
DOI: 10.1101/186056
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The synthetic histone-binding regulator protein PcTF activates interferon genes in breast cancer cells

Abstract: Disease states, such as breast cancer, arise from the disruption of chromatin, the central DNA-protein structures that package human genetic material. Mounting evidence from genome-wide studies across cancers show that Polycomb-mediated repression of sets of genes, called Polycomb modules, is strongly linked to a poor prognosis. We developed a synthetic transcriptional activator to release silenced genes from the repressed state. The Polycomb-based Transcription Factor (PcTF) is a synthetic effector that accum… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 117 publications
(143 reference statements)
0
1
0
Order By: Relevance
“…We have previously designed chromatin sensor-actuator proteins that bind histone post-translational modifications and co-activate groups of repressed genes. We demonstrated that a H3K27me3-specific sensor-actuator called PcTF activates epigenetically repressed tumor suppressor genes in several cancer cell lines [18,19] . However, experiments with epigenome editors and sensor-actuators have relied heavily on the delivery and overexpression of fusion-encoding transgenes.…”
Section: Introductionmentioning
confidence: 96%
“…We have previously designed chromatin sensor-actuator proteins that bind histone post-translational modifications and co-activate groups of repressed genes. We demonstrated that a H3K27me3-specific sensor-actuator called PcTF activates epigenetically repressed tumor suppressor genes in several cancer cell lines [18,19] . However, experiments with epigenome editors and sensor-actuators have relied heavily on the delivery and overexpression of fusion-encoding transgenes.…”
Section: Introductionmentioning
confidence: 96%